High correlations between plant clonality and ecosystem service functions after management in a chronosequence of evergreen conifer plantations - Song, Ping; Xu, Yu-Han; Yuan, Yuan; Xu, Ke-Qin; Yao, Jia-Bao; Chen, Shao-Zhi (Frontiers in Plant Science, 2023)
Climate change and mono-afforestation or mono-reforestation have continuously caused a decline in biodiversity and ecosystem services on forest plantations. Key plant functional traits in forests or plantations may affect ecosystem functions after forest management practices. Plant clonality, a key functional trait, frequently links to biodiversity and ecosystem functions and affects the biodiversityecosystem functioning (BEF) relationship. However, little is known about how plant clonality affects ecosystem functions and services of plantations after forest management. We conducted a field experiment to discuss the diversity and proportion of clonal plants, plant diversity of the communities, and ecosystem service functions and their relationships under 10 years of close-to-nature (CTN) management, artificial gap management, and control (i.e., without management) in the three stages of C. Lanceolata plantations. Our results showed that CTN and gap management modes significantly facilitated diversity of clonal plants, plant diversity of the communities, and parameters of ecosystem service functions in C. lanceolata plantations. Moreover, 2 CTN management promoted plant community diversity, soil water conservation, and carbon storage the most in the earlier stand stages. Diversity of clonal plants was significantly positively correlated with ecosystem service functions after forest management. SEM analysis indicated that forest gap or CTN management indirectly positively affected ecosystem service functions through increasing diversity of clonal woody plants and plant diversity of the communities. Our results indicate a highly positive effect of gap or CTN management on diversity and proportion of clonal plants and on plant diversity of the communities, which link to improvements in ecosystem service functions (i.e., water and soil conservation and carbon storage).The link between forest management, diversity, and ecosystem functions suggests that key functional traits or plant functional groups should be considered to underline the mechanism of traits-ecosystem functioning relationships and the restoration of degraded plantations.